Tweeting about #Diseases and #Publichealth: Communicating Global Health Issues across Nations. Issue 9 (28th July 2020) - Guidry, Jeanine P. D.; Meganck, Shana L.; Lovari, Alessandro; Messner, Marcus; Medina-Messner, Vivian; Sherman, Scott; Adams, Jay
ABSTRACT: Twitter is playing an increasing role in health communications, but little is known about the Twitter use of national health departments in general and across different nations in particular. This quantitative content analysis of 1, 200 tweets from 12 national health departments showed that the topics covered in these tweets are often lacking in broad coverage – cardiovascular disease is barely mentioned, while infectious diseases are often highlighted – and the tweets do not try to initiate engagement through creating a two-way dialogue with followers. However, the tweets appear to use Health Belief Model constructs, such as initiating cues to action, mentioning self-efficacy and highlighting perceived benefits of health preventative, treatment or screening options, and this is associated with increased Twitter engagement. The paper ends with recommendations for both future studies and new challenges for the use of Twitter by national health departments.